2017
DOI: 10.1038/cddis.2017.248
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor promotes temozolomide resistance in glioblastoma through TGF-β1-dependent activation of Smad/ERK signaling

Abstract: Limited benefits and clinical utility of temozolomide (TMZ) for glioblastoma (GB) are frequently compromised by the development of acquired drug resistance. Overcoming TMZ resistance and uncovering the underlying mechanisms are challenges faced during GB chemotherapy. In this study, we reported that connective tissue growth factor (CTGF) was associated with GB chemoresistance and significantly upregulated in TMZ-treated GB cells. CTGF knockdown promoted TMZ-induced cell apoptosis and enhanced chemosensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 49 publications
2
32
0
1
Order By: Relevance
“…Additionally, it is addressed that KDM3A, a demethylase of histone H3K9me1/2, can promote the expression of CTGF by facilitating H3K27ac on the enhancers of CTGF [22]. While CTGF promotes drug-resistance in glioblastoma cells and facilitates the progression of glioblastoma [23]. Based on what has been discussed above, it was indicated that miR-27a-3p secreted from glioblastoma-EVs could downregulate EZH1 expression, elevate expression of KDM3A and further upregulate CTGF to polarize M2 macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is addressed that KDM3A, a demethylase of histone H3K9me1/2, can promote the expression of CTGF by facilitating H3K27ac on the enhancers of CTGF [22]. While CTGF promotes drug-resistance in glioblastoma cells and facilitates the progression of glioblastoma [23]. Based on what has been discussed above, it was indicated that miR-27a-3p secreted from glioblastoma-EVs could downregulate EZH1 expression, elevate expression of KDM3A and further upregulate CTGF to polarize M2 macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…CTGF has been shown to regulate the MET of head and neck cancer cells ( 177 ) and drug resistance in glioblastoma ( 178 ), both via a mechanism involving the re-expression of pluripotency genes. Furthermore, CTGF inhibition reduces the growth of metastatic melanoma in an animal model ( 179 ).…”
Section: Molecular Regulators Of the Ecm That Influence Cancer Cell Pmentioning
confidence: 99%
“…3.2 | CCN2 increases ABCG2 expression via the α6β1 integrin receptor in human osteosarcoma cells CCN2 is capable of binding various growth factors or integrins and modifying their activity in certain carcinoma cells (Jun & Lau, 2017;Yang et al, 2016;Zeng et al, 2017). The most researched CCNbinding receptors are the integrins αvβ3, αvβ5, α5β1, and α6β1 (Lau, 2016).…”
Section: Ccn2 Enhances Abcg2 Expression and Increases Osteosarcoma mentioning
confidence: 99%
“…Around 27 human cancers have been linked to aberrant CCN2 expression (Zeng et al, 2017). CCN2 is a multifunctional signaling protein involved in a wide variety of biological and pathological processes (Bornstein & Sage, 2002;Pan et al, 2002), with some studies reporting that CCN2 promotes cell progression by supporting tumor cell survival and correlating with chemotherapeutic resistance in a variety of cancers (Corvaisier et al, 2016;Cui et al, 2011;Yin et al, 2010;Zeng et al, 2017).…”
mentioning
confidence: 99%